2019
DOI: 10.1021/acs.chemmater.9b03852
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Crystallization and Kinetic Freezing of Site-Disorder in the Lithium Superionic Argyrodite Li6PS5Br

Abstract: Lithium argyrodite superionic conductors are currently being investigated as solid electrolytes for all-solid-state batteries. Recently, in the lithium argyrodite Li6PS5X (X = Cl, Br, and I), a site-disorder between the anions S2– and X– has been observed, which strongly affects the ionic transport and appears to be a function of the halide present. In this work, we show how such a disorder in Li6PS5Br can be engineered via the synthesis method. By comparing fast cooling (i.e., quenching) to more slowly cooled… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
117
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 84 publications
(132 citation statements)
references
References 53 publications
13
117
1
Order By: Relevance
“…Exceeding the range of 8 Å, the remaining, more crystalline precursor ErCl 3 dominates the G(r) due to the low coherence length of the locally formed Li 3 ErCl 6 . This rapid crystallization within 1 min after mechanochemical milling, while surprising, was recently found to also occur in Li 6 PS 5 Br, [40] providing further evidence that mechanochemical milling already acts as a primary synthesis step leading to low coherency products and possible prenucleation clusters.…”
Section: Influence Of Synthesis On the Structure And Disordermentioning
confidence: 57%
“…Exceeding the range of 8 Å, the remaining, more crystalline precursor ErCl 3 dominates the G(r) due to the low coherence length of the locally formed Li 3 ErCl 6 . This rapid crystallization within 1 min after mechanochemical milling, while surprising, was recently found to also occur in Li 6 PS 5 Br, [40] providing further evidence that mechanochemical milling already acts as a primary synthesis step leading to low coherency products and possible prenucleation clusters.…”
Section: Influence Of Synthesis On the Structure And Disordermentioning
confidence: 57%
“…At this point, we feel a short discussion on the source of the argyrodite is needed. Li 6 PS 5 Cl can be synthesized by a high‐temperature reaction of mixtures of P 4 S 10 , Li 2 S, and LiCl as was done here, [ 61,64 ] by ball milling the same precursors (followed by short heat treatments), [ 77–79 ] or by solution chemistry from Li 2 S, Li X , and Li 3 PS 4 (which itself can be ball milled or made via solution) in a solvent such as ethanol. [ 51,80 ] It can also be bought commercially from a few suppliers, where the synthesis route is not always clear.…”
Section: Resultsmentioning
confidence: 99%
“…They reported the presence of a three-dimensional (3D) pathway network for the long-range ion conduction of all Li 6 PS 5 X (X = Cl, Br, I) phases, which consisted of interconnected low-energy local pathway cages [180]. The experimentally measured ionic conductivity at 25 • C of Li 6 PS 5 Cl, Li 6 PS 5 Br, and Li 6 PS 5 I prepared by ball milling followed by heating at 550 • C in inert atmosphere are in the range 1.9 × 10 −4 -7.0 × 10 −3 S cm −1 and calculated activation energies in the range 0.26-0.41 eV (Table 1) [180][181][182][183][184][185][186]. Further, Boulineau et al [183] reported the effect of enhancement of the conductivity of Li 6 PS 5 Cl from 2× 10 −4 S cm −1 to 1.33 × 10 −3 S cm −1 when the ball milling time varies from 1 h to 10 h. Rao and Adams [181] compared the values of E a determined by both experimental and computational method for Li 6 PS 5 X with X= Cl, Br, I in the range 0.25-0.38 eV.…”
Section: Argyrodite Electrolytesmentioning
confidence: 95%
“…(iv) The conductivities of argyrodite electrolytes depend on the preparation method, grain boundary contributions, and conductivity measurement method and fabrication technique of pelletized samples, including sintering cold-pressed pellets that influences the density of the specimens [183]. Based on previous literature studies, conductivity values are also influenced by cooling rate [186], porosity, and pore distribution [190]. Lower Li + ion conductivities, in the range of 10 −5 -10 −4 mS cm −1 , were reported when the electrolytes were synthesized via the solution-based method, which were attributed to the presence of additional impurity phases in the compounds [189].…”
Section: Argyrodite Electrolytesmentioning
confidence: 99%